Stroke among Māori in Aotearoa New Zealand and solutions to address persistent inequities - Ranta, Anna; Jones, Bernadette; Harwood, Matire (Frontiers in Stroke, 2023)
Māori, the Indigenous people of Aotearoa New Zealand (Aotearoa), experience stroke at a younger age and at a greater rate than New Zealanders of European ethnicity (NZ Europeans). These disparities have persisted for decades and recent evidence suggests that the gap is widening. Māori also experience reduced access to some key stroke-management interventions and consequently worse poststroke outcomes compared to non-Māori counterparts. Reasons for the ethnic differences in stroke rates and outcomes include differential exposure to stroke risk factors, differential access to early diagnosis and treatment, and unequal treatment. Recent Aotearoa-based research has suggested that the root causes for these ethnic inequities, including unconscious bias and institutional racism, are likely attributable to Aotearoa's colonial past and related inter-generational sequalae. With recent reforms to the national health system there is now a new mandate to actively move toward a more bicultural approach which emphasizes Indigenous rights, values, priorities, and approaches in healthcare. This presents important opportunities to address the well-described inequities using a genuine partnership model. This paper will discuss the latest evidence around stroke related health disparities affecting Māori, describe existing approaches to address inequitable health outcomes, and present additional novel avenues that are currently being explored.